Socio-demographic and ecological factors associated with anti-HCV prevalence in people who inject drugs: A systematic review. (1st April 2020) - Colledge, Samantha; Leung, Janni; Grebely, Jason; Degenhardt, Louisa; Peacock, Amy; Hickman, Matthew; Vickerman, Peter; Stone, Jack; Trickey, Adam; Larney, Sarah
Highlights: Anti-HCV prevalence was strongly associated with HIV prevalence among PWID. PWID from countries with higher development had higher anti-HCV prevalence. Opportunity to control HCV epidemic among PWID in low- and middle-income countries. Abstract: Background: The World Health Organization (WHO) aim to eliminate hepatitis C virus (HCV) as a public health threat by 2030. People who inject drugs (PWID) are a key risk group for HCV transmission globally. We explored socio-demographic and ecological variables associated with HCV antibody (anti-HCV) prevalence among samples of PWID. Methods: We systematically searched for and screened journal articles and online reports published between January 2011 and June 2017. Serologically confirmed anti-HCV prevalence among PWID and other study-level socio-demographic variables were extracted. Country-level ecological indicators were sourced from online databases. We used generalized linear models to investigate associations between anti-HCV prevalence estimates and other study-level and country-level variables. Results: There were 223 studies from 84 countries contributing 569 estimates of anti-HCV prevalence among PWID. Among study-level indicators, higher levels of anti-HCV prevalence were associated with higher HIV prevalence (B = 0.20; 95 % Confidence Interval [95 %CI] = 0.12, 0.29, p < 0.001) and year of data collection (B=−0.08; 95 %CI=−0.15, −0.02; p = 0.011). At a national level, higher Human Development Index scores (B=4.37; 95 %CI=0.12, 8.63, p = 0.044) were associated with higher levels of anti-HCV in samples. Implications: Serological surveillance data are increasingly available globally; however, there are still geographical gaps in quantification of HCV prevalence among PWID that must be addressed to inform efforts to achieve HCV elimination. Anti-HCV prevalence was lower in samples of PWID from countries with lower Human Development Index scores, which points to an opportunity to provide targeted intervention and potentially control transmission rates of infection in countries characterized by poor population health, education, and income.